2022
DOI: 10.3389/fmicb.2021.722379
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Genome Sequencing and Potassium-Solubilizing Mechanism of Bacillus aryabhattai SK1-7

Abstract: To analyze the whole genome of Bacillus aryabhattai strain SK1-7 and explore its potassium solubilization characteristics and mechanism, thus providing a theoretical basis for analyzing the utilization and improvement of insoluble potassium resources in soil. Genome information for Bacillus aryabhattai SK1-7 was obtained by using Illumina NovaSeq second-generation sequencing and GridION Nanopore ONT third-generation sequencing technology. The contents of organic acids and polysaccharides in fermentation broth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 27 publications
(28 reference statements)
0
7
0
Order By: Relevance
“…4 ). Previous studies in our laboratory showed that the aluminum and silica ion levels in the fermentation filtrate of strain SK1-7 in FM (feldspar) showed a gentle increasing trend for the first 7 days ( 34 ). It is assumed that the gradual shift to acidic conditions in the medium resulted in the release of Al 3+ , Si 4+ , etc., from potassium feldspar.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…4 ). Previous studies in our laboratory showed that the aluminum and silica ion levels in the fermentation filtrate of strain SK1-7 in FM (feldspar) showed a gentle increasing trend for the first 7 days ( 34 ). It is assumed that the gradual shift to acidic conditions in the medium resulted in the release of Al 3+ , Si 4+ , etc., from potassium feldspar.…”
Section: Discussionmentioning
confidence: 87%
“…This bacterium can effectively dissolve insoluble potassium and release soluble potassium ions, with a release rate of 32.6%. The pH of SK1-7 under incubation with an insoluble potassium source decreases rapidly in a relatively short period of time, with the strain mainly secreting malic acid, formic acid, acetic acid, and citric acid, thereby releasing potassium, silicon, and aluminum ions from potassium feldspar ( 34 ). Gupta et al ( 35 ) divided Bacillus species into 17 different branches by phylogenomic and comparative genomic analyses, and B. aryabhattai was renamed Priestia aryabhattai .…”
Section: Introductionmentioning
confidence: 99%
“…Enterococcus and Pseudomonas aeruginosa also showed P and K solubilization and improved the maize height, yield, and nutrient acquisition (Kumar et al, 2021b ). Bacillus aryabhattai showed K solubilization, protects plants from stress, and improves their growth via the expression of K-solubilizing genes (Chen et al, 2022 ).…”
Section: Types Of Biofertilizers and Their Role In Crop Production An...mentioning
confidence: 99%
“…that can be hydrolyzed into reducing sugars under the measurement conditions ( 11 , 12 ). The determination methods of total sugar content mainly include phenol-sulfuric acid method ( 2 ), anthrone-sulfuric acid method ( 13 ), full-wavelength enzyme labeling method ( 14 ), and direct titration method ( 15 ). In the current research, due to the simple detection method, good stability and high sensitivity, phenol-sulfuric acid method is widely used ( 16 ).…”
Section: Introductionmentioning
confidence: 99%